If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + -1) = 6(x + -1) Reorder the terms: 4(-1 + 3x) = 6(x + -1) (-1 * 4 + 3x * 4) = 6(x + -1) (-4 + 12x) = 6(x + -1) Reorder the terms: -4 + 12x = 6(-1 + x) -4 + 12x = (-1 * 6 + x * 6) -4 + 12x = (-6 + 6x) Solving -4 + 12x = -6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -4 + 12x + -6x = -6 + 6x + -6x Combine like terms: 12x + -6x = 6x -4 + 6x = -6 + 6x + -6x Combine like terms: 6x + -6x = 0 -4 + 6x = -6 + 0 -4 + 6x = -6 Add '4' to each side of the equation. -4 + 4 + 6x = -6 + 4 Combine like terms: -4 + 4 = 0 0 + 6x = -6 + 4 6x = -6 + 4 Combine like terms: -6 + 4 = -2 6x = -2 Divide each side by '6'. x = -0.3333333333 Simplifying x = -0.3333333333
| 23+x=19+11 | | 4x+3.75=x-6 | | Y=7/17 | | 11.3y=4052 | | (2y-5x-4)-(x-6y+5)= | | 38-4=8 | | 8(x)+10=-9 | | x+78=97 | | 8(x)+10=9 | | x-(-53)=-123 | | (-3x-y+2)+(-2x+4y-9)= | | x-(-62)=-54 | | -3(y+5)-21=0 | | 10+-18+15z+z= | | 3x-7/2=x/3 | | x-(-33)=-75 | | 3(y+5)-21=-0 | | -1.4+0.72=x | | x-(-87)=-34 | | logx+4(17-4)=2 | | x-(-11)=-45 | | x-(-91)=-21 | | -3X+2Y-3-3X+2Y+3= | | x-(-87)=-312 | | x-(-59)=-21 | | x-(-76)=-231 | | (6x-3y)-(x-6y)= | | x^5-3x^3+7x-16=0 | | x-(-41)=-53 | | Y=3.5x-2.5 | | solvex^5-3x^3+7x-16=0 | | x+312=-51 |